Psychometric Properties of the Revised Illness Perception Questionnaire for Oral Health (2023)
Aims: The aim of this study was to test the hypothesis that, for patients with dental caries, the Spanish version of the Revised Illness Perception Questionnaire for Oral Health (IPQ-R-OH) has 7 dimensions, including personal and treatment control, timeline-acute/chronic and timeline-cyclical, illness coherence, consequences, and emotional representations. Methods: A Spanish adaptation of the IPQ-R, with a self-reported 38-item scale, was developed. Exploratory and confirmatory factor analyses were conducted using data from 520 patients with dental caries attending the Dental Clinic at Universidad Cooperativa de Colombia, Pasto, Colombia. Results: Exploratory factor analysis revealed 7 dimensions with 36 items (2 items were removed because of poor factor loadings or discriminant ability). The internal consistency coefficients of each factor ranged from 0.72 to 0.91, and all item loadings were >0.52. Confirmatory factor analysis indicated that a 7-factor model with 36 items had superior fit compared to the 38-item original model: ?2 = 1,784.291 (df = 573, p < 0.001); nonnormal fit index = 0.941; comparative fit index = 0.946; root mean square error of approximation = 0.062 (90% CI = 0.057-0.066); standardized root mean square residual = 0.072; and Akaike information criterion = 638.291. Control (integrated by items from personal control, treatment control, and timeline-acute factors) and hopelessness (PC15 and PC17) were the 2 reconfigured factors that were identified. Conclusions: These findings suggest that the modified 36-item model has satisfactory reliability and construct factorial validity; therefore, it could be a valuable instrument in the screening of illness perceptions in oral health. © 2017 S. Karger AG, Basel. All rights reserved.